Loan To Deposit Ratio, Capital Adequacy Ratio, Return On Equity Dan Bopo Dalam Menilai Kinerja Keuangan Pt. Bank Bni Syariah - Noviantoro, Rinto; Herlin, Herlin (Jurnal BAABU AL-ILMI: Ekonomi dan Perbankan Syariah, 2019)
Abstract. The purpose of this study is to determine the financial performance of PT. Bank BNI Syariah. The method of collecting data in this study is documentation. documentation, namely data collection through financial statements in the form of balance sheets and profit / loss statements. Â Loan Deposit Ratio (LDR) from 2015-2017 it was 89.14%, 84.01% and 78.89%.the Capital adequacy ratio and the Debt to equity ratio have been determined if the ratio produced is <50% - 75%. Return on equity have been determined to produce a ratio of> 1.5% and at BOPO â‰¤93.52%. From the perspective of the Capital Adequacy Ratio, in 2015-2017 the value was 38.45%, 64.84% and 38.50%By using BOPO in 2015-2017 the value was 83.21%, 80.75% and 80.91%. While the return on equity in 2015-2017 is 1.18%, 1.18% and 0.93%